Risk of presentation to hospital with epileptic seizures after vaccination with monovalent AS03 adjuvanted pandemic A/H1N1 2009 influenza vaccine (Pandemrix): self controlled case series study. (28th December 2012) - Arnheim-Dahlström, Lisen; Hällgren, Jonas; Weibull, Caroline E; Sparén, Pär
Abstract : Objective To assess the risk of epileptic seizures in people with and without epilepsy after vaccination with a monovalent AS03 adjuvanted pandemic A/H1N1 influenza vaccine (Pandemrix; Glaxo SmithKline, Sweden). Design Register based self controlled case series. Setting Three Swedish counties (source population 750 000). Participants 373 398 people (age 0-106, median 41.2) who were vaccinated. Vaccinated people with epileptic seizures, diagnosed as inpatients or outpatients, at any time from 90 days before until 90 days after any dose of vaccine. Main outcome measures Endpoints were admission to hospital or outpatient hospital care with epileptic seizures as the main diagnosis. The effect estimate of relative incidence was calculated as the incidence of epileptic seizures in period after exposure relative to the incidence of epileptic seizures in two control periods, one before and one after vaccination. Results 859 people experienced epileptic seizures during the study period. There was no increased risk of seizures in people with previously diagnosed epilepsy (relative incidence 1.01, 95% confidence interval 0.74 to 1.39) and a non-significant decrease in risk for people without epilepsy (0.67, 0.27 to 1.65) during the day 1-7 risk period (where day 1 is the day of vaccination). In a second risk period (day 8-30), there was a non-significant increased risk of seizures in people without epilepsy (1.11, 0.73 to 1.70) but no increase in risk for those with epilepsy (1.00, 0.83 to 1.21). Conclusions This study found no evidence of an increase in risk of presentation to hospital with epileptic seizures after vaccination with a monovalent AS03 adjuvanted pandemic H1N1 influenza vaccine.